Relações entre habilidades socioemocionais e inovação para alguns licenciados em ciências biológicas - Paranhos, Márcia Cristina Rocha (2017)
The concept of Socio-Emotional Skills is about how individuals can reflect on their emotions when they need to make intrapersonal and interpersonal decisions. It is, therefore, the reflexive capacity to deal with the emotions and to potentiate unique characteristics of oneself in the relations with the other. In the educational field, such skills are built by a complex network of knowledge and behaviors related to the success or failure of an enterprise, which aims to innovate pedagogically. In this sense, we propose to understand the relations between innovation and Socio-Emotional Skills from the statements of some undergraduate students of Biological Sciences of the Federal University of Sergipe. The work is organized in two phases: in the first, exploratory, we identified some episodic cases, observed in a mini course that dealt with the issue of Socio-Emotional Skills, in which some students of this degree participated; In a second moment, five semi-structured interviews were recorded, transcribed and analyzed in three moments. In the first, from five categories established a priori, equivalent to the domains of personality, to know: 1) openness to new experiences, 2) Consciousness, 3) Extroversion, 4) Cooperativity and 5) Emotional Stability. In the second moment, we created five categories a posteriori: 1) Innovation: opposition between conservatism and openings to changes; 2) Innovation as a proposal of school methodology; 3) Innovation as a management organization proposal and 4) Innovation as a proposal for curricular change. Finally, in the third and final moment, we tried to compare if students with certain indicators for certain HSE, presented what kind of conceptions about innovation. Among the results, we noticed that during the mini-course, the students expressed their HSE, although shyly, since they presented difficulties in speaking of their own characteristics, internalizing their emotions. Regarding the analysis of the interviews, we noticed that the category Consciousness contained more frequency of the presented discourses in relation to the other categories. This leads, therefore, to the understanding that for the interviewees, the development of skills such as responsibility, discipline and organization would be the driver of satisfactory academic performance, within what is required as a technical skill by the curriculum to future graduates. When we refer to the analysis of innovation categories, we notice that the discourses are associated with innovative practices and methodologies, since they were presented more frequently in the Innovation category as a school methodology. When we look for the relations between the categories of HSE and innovation, we understand that the category of consciousness is related to methodological innovations, and the lack of cooperativity tends to be related to the barriers that inhibit innovations. When we think of the analysis by subjects, we understand that the most socially-balanced individuals tend to contribute to all categories of innovation. More cooperative individuals innovate methodically, while those who are not open to new experiences and those who have contributed most in the emotional stability category tend to find barriers to innovation.